2020
DOI: 10.1002/advs.202001242
|View full text |Cite
|
Sign up to set email alerts
|

Rising Temperature May Trigger Deep Soil Carbon Loss Across Forest Ecosystems

Abstract: Significantly more carbon (C) is stored in deep soil than in shallow horizons, yet how the decomposition of deep soil organic C (SOC) will respond to rising temperature remains unexplored on large scales, leading to considerable uncertainties to predictions of the magnitude and direction of C-cycle feedbacks to climate change. Herein, short-term temperature sensitivity of SOC decomposition (expressed as Q 10) from six depths within the top 1 m soil from 90 upland forest sites (540 soil samples) across China is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 68 publications
2
32
0
Order By: Relevance
“…The functional redundancy in the decomposition processes was shown to decrease with increasing C recalcitrance (Maron et al, 2018). Third, the failure to capture causal relations between the tested biotic and abiotic variables and Q 10 by the SEM analysis in the topsoil implies that the relative importance of soil microbes is attenuated by other factors, for example, climate, soil environments, substrate availability (Gillabel et al, 2010; Li, Pei, et al, 2020; Suseela et al, 2012), regulating the stability of SOC decomposition. For example, using soils from 90 upland forest sites, Li, Pei, et al (2020) showed that climate but not microbes was the primary regulator of Q 10 in shallow soils.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The functional redundancy in the decomposition processes was shown to decrease with increasing C recalcitrance (Maron et al, 2018). Third, the failure to capture causal relations between the tested biotic and abiotic variables and Q 10 by the SEM analysis in the topsoil implies that the relative importance of soil microbes is attenuated by other factors, for example, climate, soil environments, substrate availability (Gillabel et al, 2010; Li, Pei, et al, 2020; Suseela et al, 2012), regulating the stability of SOC decomposition. For example, using soils from 90 upland forest sites, Li, Pei, et al (2020) showed that climate but not microbes was the primary regulator of Q 10 in shallow soils.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the failure to capture causal relations between the tested biotic and abiotic variables and Q 10 by the SEM analysis in the topsoil implies that the relative importance of soil microbes is attenuated by other factors, for example, climate, soil environments, substrate availability (Gillabel et al, 2010; Li, Pei, et al, 2020; Suseela et al, 2012), regulating the stability of SOC decomposition. For example, using soils from 90 upland forest sites, Li, Pei, et al (2020) showed that climate but not microbes was the primary regulator of Q 10 in shallow soils. We did not observe a significant correlation between Q 10 and mean annual temperature or growing season precipitation, suggesting the complexity in the controlling factors of Q 10 in different regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil carbon quality has long been recognized as a control on the temperature response of soil microbial respiration (Conant et al, 2008; Craine et al, 2010; Fierer et al, 2006; Li et al, 2017; Li, Pei, Pendall, Reich, et al, 2020; Wang et al, 2018). The carbon quality‐temperature (CQT) hypothesis suggests that decomposition of low‐quality carbon requires high activation energy and thus is more sensitive to temperature change (Davidson & Janssens, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…To do this, soils (passed through a 0.15 mm mesh sieve) was dried at 60°C and homogenized by grinding. Reflectance spectra (400–4000 cm −1 ) were obtained using a FT‐IR (Nicolet iS5, Thermo Scientific; Li, Pei, Pendall, Reich, et al, 2020) and relative peak areas were calculated, which represent the relative abundance of different organic carbon functional groups, such as carbohydrates (1024 cm −1 ) and aromatic carbon groups (1637 cm −1 ; Hodgkins et al, 2018). A higher ratio of carbohydrates to aromatics is usually considered as higher soil carbon quality (Tfaily et al, 2014).…”
Section: Methodsmentioning
confidence: 99%